SINTESIS DAN KARAKTERISASI HIDROGEL SUPERABSORBEN PATI ONGGOK SEBAGAI PLESTER PENURUN DEMAM - Febri Ramdhani; Salih Muharam; Lela Lailatul Khumaisah (AGITASI: Jurnal Teknik Kimia, 2026)
People in general still use the traditional way to reduce fever by using a cloth moistened with water. In this era of advanced technology, fever-reducing plasters can be used to reduce fever more effectively. One of the materials that can be used to make fever-reducing plaster is superabsorbent hydrogel. The superabsorbent hydrogel was prepared from cassava starch using the cross-linking method with the addition of epichlorohydrin and carboxymethyl. The stages of the research carried out were starch-epichlorohydrin-carboxymethyl synthesis, measurement of swelling ratio, effectiveness of superabsorbent hydrogel plaster on the speed of temperature reduction as an indicator of reducing fever. The results showed that the starch-epichlorohydrin swelling ratio was 300% and increased to 994% with the addition of carboxymethyl. The starch-epichlorohydrin-carboxymethyl superabsorbent hydrogel has the ability to reduce the water temperatu